Thermal runaway mechanism of lithium-ion battery with LiNi0.8Mn0.1Co0.1O2 cathode materials. (July 2021) - Li, Yan; Liu, Xiang; Wang, Li; Feng, Xuning; Ren, Dongsheng; Wu, Yu; Xu, Guiliang; Lu, Languang; Hou, Junxian; Zhang, Weifeng; Wang, Yongling; Xu, Wenqian; et al.
Abstract: Battery safety is critical to the application of lithium-ion batteries, especially for high energy density battery applied in electric vehicles. In this paper, the thermal runaway mechanism of LiNi0.8 Co0.1 Mn0.1 O2 based lithium-ion battery is illustrated. And the reaction between cathode and flammable electrolyte is proved as the trigger of the thermal runaway accident. In detail, with differential scanning calorimeter tests for battery components, the material combination contributing to thermal runaway was decoupled. Characterization with synchrotron X-ray diffraction and transmission electron microscopy with in-situ heating proved that the vigorous exothermic reaction is initiated by the liberated oxygen species. The pulse of highly active oxygen species reacted quickly with the electrolyte, accompanied with tremendous heat release, which accelerated the phase transformation of charged cathode. Also, the mechanism is verified by a confirmatory experiment when the highly active oxygen species were trapped by anion receptor, the phase transformation of the charged cathode was inhibited. Clarifying the thermal runaway mechanism of LiNi0.8 Co0.1 Mn0.1 based lithium-ion battery may light the way to battery chemistries of both high energy density and high safety. Graphical Abstract: ga1 Highlights: The thermally driven oxygen release pathway is strongly depended on the exposed chemical environment. The cathode liberated oxygen species (O2, O 2-, O -, etc.) is considered to be blamed for the thermal runaway. The reaction between oxygen species and electrolyte is the triggering factor of thermal runaway.